Will Familial Hypercholesterolaemia Cohorts Hide Many More Lisosomal Acid Lipase Deficiency Patients? - Chora, J.R. (2018)
Aims: Lisosomal Acid Lipase Deficiency (LALD), historical known as Cholesterol Ester Storage Disease (CESD), is an autosomal lisosomal storage recessive disorder and an unrecognized cause of dyslipidaemia. Mutations in LIPA gene are the underlying cause of LALD, being a mutation in the splice site of exon 8 the most common cause of the disease. Patients with LALD present dyslipidaemia and altered liver function. The aim of this work was to analyze LIPA gene in patients with unexplained dyslipidaemia.